Оn the problem of the 240 K singularity in water. (25th October 2020) - Volkov, A. A.; Vasin, A. A.; Volkov, A. A.
Abstract: Water's properties are exceptional at low temperatures. Dielectric constant demonstrates ferroelectric-like behavior. We treat an idea to interpret the fundamental feature of water, 240 K singularity, through the Maxwell speed distribution of freely moving water molecules. We use the ion-molecular model recently proposed by us, in which water molecules make the translation-oscillator movement with rapid potential/kinetic energy transformation. The model provides direct access to the velocity distribution through the kinetic energy of free thermal motion.